The development of an alternative model for undertaking “voluntary work” as industrial training - Selke, Raimond; Schaar, Torsten (2013)
The new “Industrial Training” course requires foreign language students in the Universiti Putra Malaysia (UPM) to gain practical experience in their foreign language skills, e.g. French, German. Commencing semester break July/August 2014, the first student batch will undertake this training. Therefore, the main aim of this paper is to develop a scenario of how to achieve the best outcomes for the students in the German Bachelor program and for the involved companies. The course outline details the learning objectives as defined in the ‘Universiti Putra Malaysia Guidelines’. For internships, teaching staff must confirm suitable organisations. Most colleagues’ efforts have so far focused upon contacting companies with overseas connections, as they should identify suitable organisations and allocate students accordingly. The course outline states “relate the knowledge learned in real situations at the workplace” and a principal new “Industrial Training” target is the use of FBMK acquired foreign language skills. At this early stage, many lecturers have already taken efforts to understand the potential opportunities of new “Industrial Training”. Whilst the „Industrial Training” has been implemented for many years in other faculties and in the Department of Communication in UPM and the Guidelines may have driven most of our teaching staff to focus on for-profit companies, we believe that students can also achieve valid “Industrial Training” results through “Volunteer Work” or training in not-for-profit organisations. This possibility exists in many Malaysian foreign language based not-for-profit organizations, e.g. Public and International Schools, national and international cultural institutes, national hospitals etc. Our research methodology comprises four consecutive stages with each stage containing questionnaires, (stage I), selected interviews, (stage I and II), or field research, (stage III). We shall subsequently identify the positive aspects of our observations and attempt to translate them into a model for other units and departments in the Faculty of Modern Languages (FBMK) in UPM, (stage IV). In some cases, we aim to develop a strategy for students to achieve all of the objectives through “Volunteer Work”. This example can subsequently be used by other faculties in UPM for “Volunteer Work” in other nonprofit organisations, and will effectively widen the horizon of “Industrial Training”.